Digital Storytelling Skills of Teacher Education Students - Cariño, Kaecy Valerine; Anog, Lorie; Agullana, Micha-ela; Medrano, Jesrael (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital storytelling is regarded as a pedagogical tool that can engage students in meaningful learning. As a result, the importance of digital storytelling has become more necessary among teachers to make learning more meaningful even in the online setup. This study was conducted to assess the digital storytelling skills of the 3rd year Teacher Education students of a Catholic University in Northern Philippines. A quantitative research design employing a descriptive method was used to assess the digital storytelling skills of the participants. The results of the study revealed that there is no significant difference in the digital storytelling skills of the participants, whether they are grouped according to major or field of specialization, in which participants gained low scores, implying that they need improvement in their digital storytelling skills.